2014
DOI: 10.1177/003335491412900613
|View full text |Cite
|
Sign up to set email alerts
|

On Academics: Advancing the Science and Practice of Dissemination and Implementation in Health: A Novel Course for Public Health Students and Academic Researchers

Abstract: Dissemination and implementation (D&I) scienceand the closely related fields of knowledge translation, scale-up/spread, and quality improvement 1-4-is critically important for bridging the research-to-practice gap and accelerating the movement of evidence-based practices, programs, and interventions into real-world settings to have an impact on population health. Indeed, D&I science has witnessed substantial growth during the past few decades, with increasing interest among researchers, practitioners, funding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…sampling using faculty of the above programs and review of the Implementation Network listserv content, which publicizes D&I research training opportunities to over 2000 subscribers every month [10]. The meeting co-chairs, themselves core faculty of multiple D&I research training courses, invited 14 individuals primarily involved in D&I research training, as faculty, course directors and trainees, identified through the searches referred to above.…”
Section: Case Studymentioning
confidence: 99%
“…sampling using faculty of the above programs and review of the Implementation Network listserv content, which publicizes D&I research training opportunities to over 2000 subscribers every month [10]. The meeting co-chairs, themselves core faculty of multiple D&I research training courses, invited 14 individuals primarily involved in D&I research training, as faculty, course directors and trainees, identified through the searches referred to above.…”
Section: Case Studymentioning
confidence: 99%
“…Articles spanned a 13-year period (2006–2019) with the majority published during or post 2014 ( N = 21) [ 18 , 47 , 57 , 58 , 62 , 88 103 ] and 10 articles published pre 2014 ( N = 10) [ 48 , 49 , 104 – 111 ]. Publications originated from 8 countries: the USA ( N = 21) [ 18 , 48 , 57 , 58 , 62 , 88 – 90 , 92 96 , 98 101 , 103 , 104 , 108 , 109 ], Canada ( N = 3) [ 106 , 107 , 110 ], Australia ( N = 2) [ 49 , 91 ], the UK ( N = 1) [ 105 ], Sweden ( N = 1) [ 47 ], Kenya ( N = 1) [ 97 ], Germany ( N = 1) [ 102 ] and Saudi Arabi ( N = 1) [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the conclusion of the week, the course was positively assessed by the trainees in terms of relevance to their needs/interests, appropriate teaching strategies and gain in confidence in ability to apply the skills and knowledge gained. A university course designed to expand training opportunities in D&I science for public health students and academic researchers, provided by the University of Alabama in 2012–2013, was evaluated by Norton [ 9 ]. The course was found effective for simultaneously teaching students and academic researchers about D&I science.…”
Section: Introductionmentioning
confidence: 99%